Exploration of the antiviral mechanism of gypsum-licorice compatibility pairing in Ma-Xing-Shi-Gan decoction from the perspective of metal-organic supramolecular interactions - Lu, Chang; Ma, Ying; Zhao, Haoyu; Zheng, Yu; Zhao, Qun; Lin, Lili; Chen, XiuZhen; Chen, Linwei; Li, Gang; Chen, Rui (Frontiers in Medical Technology, 2025)
The efficacy of the gypsum-licorice (SG-GC) pair was evaluated through its in vivo and in vitro anti-respiratory syncytial virus (RSV) activity. The results showed that SG-GC had significant efficacy against RSV infection in mice, which was close to that of the whole formula, and could significantly reduce the viral load in the lungs, improve the symptoms of lung injury, and reduce the inflammatory cell infiltration in the pathological sites. The decoction of single-flavored gypsum showed some anti-RSV efficacy, but not significant; when combined with sub-inhibitory concentrations of GA, it showed a significantly enhanced anti-RSV effect. The experimental results of this study suggest that gypsum may be a potential key antiviral substance, but its efficacy needs to be complemented by licorice; the significant enhancement of antiviral efficacy of SG-GC may be related to the formation of metal-organic supramolecules after the interaction of trace metal ions in gypsum and GA in licorice.